Analysing wellbeing using Islamic indicators: a multidimensional perspective / Mohamed Saladin Abdul Rasool, Hamidah Irpan and Siti Mariam Ali - Abdul Rasool, Mohamed Saladin; Irpan, Hamidah; Ali, Siti Mariam (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Wellbeing is an important aspect of human life. In consists of various aspects such as material (financial), relational (family) and subjective (psychological). From an Islamic perspective, wellbeing is viewed in various ways. Normally it is based on Maqasid al-Shariah principles. The objective of the present paper is to discuss wellbeing using the five dimensions or principles of Maqasid al-Shariah, namely religiosity, wealth, physical self, posterity and knowledge. Each dimension will be represented by appropriate variables. The cross-section data employs a simple systematic random sampling in of Alor Gajah district with one of the highest scores of Malaysian Wellbeing Index 2016. Descriptive analysis and correlation were undertaken in this quantitative study with a sample size of 160 Muslim household heads. The correlation analysis revealed various relationship between each Maqasid dimensions. Thus, role of zakat in addressing each dimension could be determined.